The pool fire case for pressure relief: Radiation exposure limited by fuel supply. Issue 3 (18th October 2014) - Sielegar, Debby; Self, Freeman
<x xml:space="preserve">Abstract</x> In design of pressure relief systems, a pool fire is one of the most typical relief cases. The first step in the fire relief calculation is determining the heat flux input from the fire and methods include the simple to the very complex, covering a myriad of factors and configurations. This article illustrates one method where the heat input is limited by the fuel supply. This method complements one traditional method where the heat input is limited by the equipment exposed area. The scope of the article is limited to the calculation of the heat release, and does not discuss the behavior of the fluid in subject equipment, the relief rate or relief device sizing. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 214–219, 2015